Surgical treatment of degenerative lumbar kyphosis (literature review) - Piontkovsky, Valentyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
An analytical review of scientific information on surgical treatment of degenerative lumbar kyphosis have been represented. It outlines the main stages of history of development of a trend in vertebrology which is associated with correction of kyphotic deformity of the lumbar spine as well as with evolution of the spinal implants and surgical approaches to treatment of patients with this pathology. Information on normal values of segmental and total lumbar lordosis as well as on common surgical procedures for correction of lumbar kyphosis have been represented. Correlation between the lumbar-pelvic balance and sagittal lumbar contour was revealed. Perspectives of scientific research in this direction were targeted.